Middleground: Siting Dispossession. Canadian Centre for Architecture, Montreal, Quebec - Moore, Kate (Archivaria, 2022)
Middleground: Siting Dispossession. Canadian Centre for Architecture, Montreal, Quebec. February 10, 2021 – March 13, 2022. Curated by Ella den Elzen, Rafico Ruiz, and Camille Saade- Traboulsi.